2013
DOI: 10.2196/jmir.2441
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality for Enhancing the Cognitive Behavioral Treatment of Obesity With Binge Eating Disorder: Randomized Controlled Study With One-Year Follow-up

Abstract: BackgroundRecent research identifies unhealthful weight-control behaviors (fasting, vomiting, or laxative abuse) induced by a negative experience of the body, as the common antecedents of both obesity and eating disorders. In particular, according to the allocentric lock hypothesis, individuals with obesity may be locked to an allocentric (observer view) negative memory of the body that is no longer updated by contrasting egocentric representations driven by perception. In other words, these patients may be lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
143
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(155 citation statements)
references
References 44 publications
2
143
0
10
Order By: Relevance
“…CBT with a VR body image treatment was found to be more effective than traditional CBT for eating disorders [61]. Similarly, Cesa et al [62] found CBT mixed with VR was more effective at reducing weight in patients with binge eating disorders compared to traditional CBT. In an innovative study, Keizer et al [60] created a full body illusion treatment, the study concluded that disturbed experiences of the body in patients with anorexia nervosa could be altered with VR.…”
Section: Eating Disordersmentioning
confidence: 93%
See 1 more Smart Citation
“…CBT with a VR body image treatment was found to be more effective than traditional CBT for eating disorders [61]. Similarly, Cesa et al [62] found CBT mixed with VR was more effective at reducing weight in patients with binge eating disorders compared to traditional CBT. In an innovative study, Keizer et al [60] created a full body illusion treatment, the study concluded that disturbed experiences of the body in patients with anorexia nervosa could be altered with VR.…”
Section: Eating Disordersmentioning
confidence: 93%
“…These varied from body image disturbance (BID) [58,59], anorexia and bulimia nervosa [55][56][60][61], food cravings [57] and obesity [62]. VR's visual ability to induce cravings led to specific virtual reality craving exposure therapy (VRCET) being the most common form of intervention [55,57,63].…”
Section: Eating Disordersmentioning
confidence: 99%
“…Los resultados mostraron pérdida de peso al año de seguimiento. Por el contrario, los participantes en el grupo, no intervenido, recuperaron en promedio la mayor parte del peso que habían perdido durante el programa de hospitalización 24 . En el caso de la anorexia nerviosa, se ha utilizado la RV bajo el supuesto de la experiencia distorsionada persistente del tamaño de su cuerpo, en donde se ha investigado si una ilusión del cuerpo completo afecta la estimación del tamaño corporal de las partes del cuerpo, con estimulación visotáctil sincrónica.…”
Section: Trastornos Alimentariosunclassified
“…VR has been used to assess and treat a wide variety of medical, surgical, psychiatric, and neurocognitive conditions including pain [1,2,4,9,13,18], addiction [20][21][22][23][24][25], anxiety disorders [3,6,7,15,[26][27][28][29][30][31][32][33][34][35], schizophrenia [10,11,[36][37][38][39][40], eating disorders [1,[41][42][43][44][45][46][47][48], stroke rehabilitation [5,16,[48][49][50][51], vestibular disorders [52], and movement disorders [53]<...>…”
Section: Introductionmentioning
confidence: 99%